Between Text and Social Media: Interpretation of Hadith Bid’ah in Salafi and Nahdlatul Ulama Discourse: Antara Teks dan Media Sosial: Interpretasi Hadits Bid'ah dalam Diskursus Salafi dan Nahdlatul Ulama - Achmad Hasibul Ma'arif; Moh. Iza Al Jufri; Mega Laela Akhiru Nahar (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2024)
The concept of ikhtilāf al-ḥadīth, once understood as a substantive contradiction between hadiths, has shifted in meaning in the digital age. Today, contestation often arises not from textual conflict but from differing interpretations among religious groups. This study aims to explore the contestation surrounding hadiths on bid’ah (religious innovation) between the Salafi and Nahdlatul Ulama (NU) paradigms on social media. It addresses two key questions; first, how do Salafi and NU groups interpret bid’ah hadiths on social media; and second, what forms of contestation emerge between these groups? Employing a qualitative-descriptive method and purposive sampling for data collection, the study finds that the Salafi group tends to adopt a textualist approach, leading to partial and concise interpretations of bid’ah hadiths on social media. In contrast, the NU group applies a contextualist approach, producing broader and more comprehensive meanings. A clear instance of contestation is observed when the Salafi-affiliated YouTube channel @MajelisilmuTV posted a video about bid’ah, which was critically countered by NU-affiliated interpretations via an Instagram post by @Ajir_Ubaidillah. This interaction illustrates how social media has become a new arena for contemporary religious debates, reflecting a transformation in the dynamics of authority and authenticity in hadith interpretation within the digital public sphere.